Le lit dit « de François Ier » de la collection Du Sommerard : des questions en attente de réponses - Muriel Barbier (In Situ)
The Musée national de la Renaissance at Écouen today possesses a bed (inventory number. E. Cl. 113) that Alexandre Du Sommerard claimed to have purchased from a Savoyard bishop who had acquired it at a sale in Paris of objects from the former royal furniture repository (Garde-Meuble de la Couronne). The earliest description of this bed dates from 1834 and presents it as a Renaissance masterpiece. At the Cluny museum, the bed was exhibited in a room known as the ‘François Ier chamber’, and, over time, the bed itself became known as the ‘François Ier’ bed. Subsequently, throughout the nineteenth and twentieth centuries, the bed was published as an outstanding example of Renaissance furniture. In most of these publications, the story told by Alexandre Du Sommerard is repeated and only rarely called into question. In all the publications, the François Ier bed is illustrated by engravings or photographs, adorned with Gondi-Lesdiguières hangings (inventory. E. Cl. 1204) or with other bed linen. But serious questions have recently been raised regarding the date of this piece of furniture. In addition, the similarities between this bed and engravings of furniture by Jacques Androuet Du Cerceau, along with the heterogeneity of the sculpted ornaments from one part of the bed to another, makes it possible to hypothesise that the bed is in fact an assembly of elements of various origins. In the context of changing its fabrics with a view to renewing its presentation in the museum, this ‘François Ier’ bed raises the question of the choices to be made by curators, conservators and upholsterers in terms of the kinds of textile suitable for a bed which is clearly of eclectic origins.